2011
DOI: 10.1016/j.jfa.2011.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Banach spaces of universal disposition

Abstract: In this paper we present a method to obtain Banach spaces of universal and almost-universal disposition with respect to a given class $\mathfrak M$ of normed spaces. The method produces, among other, the Gurari\u{\i} space $\mathcal G$ (the only separable Banach space of almost-universal disposition with respect to the class $\mathfrak F$ of finite dimensional spaces), or the Kubis space $\mathcal K$ (under {\sf CH}, the only Banach space with the density character the continuum which is of universal dispositi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 19 publications
0
68
0
Order By: Relevance
“…Gurariy conjectured the existence of Banach spaces of universal disposition, as well as of spaces of universal disposition with respect to the class S of separable spaces. This conjecture was proved to be true in [1], where a general method to construct spaces of universal disposition with respect to different classes was presented. In particular, it was shown that the space that Gurariy conjectured is isometric to the Fraïssé limit, in the category of separable Banach spaces and into isometries, constructed by Kubiś [22].…”
Section: Introductionmentioning
confidence: 91%
“…Gurariy conjectured the existence of Banach spaces of universal disposition, as well as of spaces of universal disposition with respect to the class S of separable spaces. This conjecture was proved to be true in [1], where a general method to construct spaces of universal disposition with respect to different classes was presented. In particular, it was shown that the space that Gurariy conjectured is isometric to the Fraïssé limit, in the category of separable Banach spaces and into isometries, constructed by Kubiś [22].…”
Section: Introductionmentioning
confidence: 91%
“…The push-out and pull-back constructions. A thorough description of the pull-back and push-out constructions in Banach spaces can be seen in [4,3,9]. Everything we need to know for this paper is that given an exact sequence (1) and an operator t : Y → B there is a commutative diagram…”
Section: Exact Sequencesmentioning
confidence: 99%
“…It can be proved (see [11,Theorem 6.1.8] or [12,Theorem 13.9]) that if U is countably incomplete and ℵ-good, then every family of less than ℵ internal subsets of S i U having the finite intersection property has nonempty intersection. Since |Γ × N| < ℵ and U is ℵ-good, there is x ∈ X i U in the nonempty intersection A combination of [4] and [3], see also [5], shows that there exist universally 1-separably injective spaces not isomorphic to any C(K) space. A higher cardinal generalization is as follows.…”
Section: Ultraproductsmentioning
confidence: 99%
“…The paper [2] started the study of spaces of universal disposition after Gurariy [10]. All available results and several new were then presented in Chapter 4 of the monograph [4].…”
mentioning
confidence: 99%
“…• Spaces of S-universal disposition are 1-separably injective [2] and [4,Thm. 3.5]. • There are spaces of F-universal disposition that are not separably injective.…”
mentioning
confidence: 99%